An integrated sampler for shipboard underway measurement of dimethyl sulfide in surface seawater and air. (15th July 2019) - Zhang, Miming; Gao, Wei; Yan, Jinpei; Wu, Yanfang; Marandino, Christa A.; Park, Keyhong; Chen, Liqi; Lin, Qi; Tan, Guobin; Pan, Meijiao
Abstract: Dimethyl sulfide (DMS), a marine-derived trace gas, can influence atmospheric compositions and has an impact on the global climate. To date, obtaining continuous and coupled shipboard underway measurements of DMS in seawater and air has been challenging. To address this issue, we report a custom-made sampling device based on the purge-and-trap technique. This sampler, in combination with a time-of-flight mass spectrometer (TOF-MS), was successfully utilized to perform coupled shipboard underway measurements of DMS in surface seawater and air around western Antarctica during the 34th Chinese Antarctic Research Expedition from February 2018 to April 2018. The seawater and air streams were continuously introduced into the sampler unit and subsampled every 10 min. The limits of detection (LODs) of DMS in seawater and air were found to be 0.07 nM and 32 pptv, respectively. The variability in the DMS levels in the surface seawater and air can be distinguished and evaluated based on the variations in the DMS peaks. These results demonstrated that the sampling device was effective for consistent, sensitive underway measurements of DMS. Graphical abstract: Image 1 Highlights: A sampler is developed for shipboard underway detecting seawater and air DMS. Surface seawater and air DMS can be detected every 10 min by the system. The system enabled measurements of long-term shipboard underway investigations.